2017
DOI: 10.1016/j.infsof.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the EASE 2016 special section: Evidence-based software engineering: Past, present, and future

Abstract: The International Conference on Evaluation and Assessment in Software Engineering (EASE) had its twentieth anniversary in 2016, with that year's edition hosted in Limerick, Ireland. Founded in 1997, the EASE conference was the first event solely dedicated to encouraging empirical research in software engineering, and its founders have been longtime advocates of evidence-based software engineering (EBSE). In this editorial, we briefly look back at the history of EBSE and the EASE conference. We then introduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…ere has been a rapid surge in the popularity of using the Evidence-Based Software Engineering (EBSE) among researchers due to the applicability of systematic literature review (SLR) in various domains [41][42][43]. e key goal of the SLR study is to systematically identify, classify, and thoroughly synthesize any new evidence based on the data extracted from the selected research publications.…”
Section: Slr Research Methodologymentioning
confidence: 99%
“…ere has been a rapid surge in the popularity of using the Evidence-Based Software Engineering (EBSE) among researchers due to the applicability of systematic literature review (SLR) in various domains [41][42][43]. e key goal of the SLR study is to systematically identify, classify, and thoroughly synthesize any new evidence based on the data extracted from the selected research publications.…”
Section: Slr Research Methodologymentioning
confidence: 99%
“…In recent years, the paradigm of Evidence-Based Software Engineering (EBSE) and its two main research methods, the systematic mapping studies (SMS) and the systematic literature reviews (SLR) have gained great notoriety [18][19][20][21]. Both tools provide a research method that systematically identifies, classifies and analyses the data reported in scientific publications (the evidence).…”
Section: Introductionmentioning
confidence: 99%